Exploring the link between sweet taste and fat (creaminess) perception, dietary intake and metabolic health in women : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Sciences at Massey University, Auckland, New Zealand - Jayasinghe, Shakeela Nathalia (Massey University, 2019)
Taste perception plays an important role in dietary choice and intake. There is a significant link between the current obesogenic food environment of ubiquitously available, highly palatable, sugar- and fat-rich foods and adverse metabolic health outcomes. Therefore, it is important to understand the nature of the link between sweet and fat taste perception and dietary intake. Using a multi-disciplinary approach employing sensory science, dietary assessment methods and metabolic health and endocrine analyses, this thesis investigated the relationship between sweet taste and fat (creaminess) perception, dietary intake and metabolic health in women to understand factors contributing or leading to obesity. The experimental study in Chapter 3 investigated the relationship between four different psychophysical measurements of sweet taste perception and explored which measurements of sweet taste perception relate to sweet food intake. An interesting finding of this chapter was the dose-dependent change in the relationship between sweet taste intensity and hedonic liking, which illustrated that sweet hedonic liking was dependent on the magnitude of sweetness experienced. Importantly, this experimental study showed for the first time a clear dose-dependent link between a lower perceived sweet taste intensity and higher sweet hedonic liking and increased intakes of total energy and carbohydrate (starch, total sugar). Chapter 4 assessed whether sweet taste and fat (creaminess) perception differ across ethnic groups with known differences in metabolic disease and obesity risk (New Zealand European, Māori, Pacific) and across body composition groups based on body mass index and body fat. Furthermore, this chapter explored whether there is a link between taste perception and metabolic and endocrine biomarkers associated with adiposity and appetite. The overall findings showed no significant differences in sweet taste and fat (creaminess) perception between ethnic groups or body composition groups. Further, no robust links between sweet taste and fat (creaminess) perception and metabolic and endocrine biomarkers were found. The study described in Chapter 5 explored the links between dietary patterns, body composition, macronutrient intakes and metabolic and endocrine biomarkers of adiposity and appetite. Higher intakes of the ‘refined and processed’ dietary pattern was linked with higher total energy and percentage carbohydrate (starch, total sugar) intakes and higher body composition measurements (e.g., body mass index, body fat). Furthermore, higher intakes of the ‘refined and processed’ dietary pattern was linked with higher circulating levels of leptin and insulin and lower levels of ghrelin. Together these findings indicated a diet-induced metabolic dysregulation in women with higher intakes of the ‘refined and processed’ dietary pattern. The research study in Chapter 6 investigated whether body composition, dietary intake and metabolic and endocrine biomarkers differ between women with distinct patterns of sweet and fat (creaminess) hedonic liking. The overall results showed that higher hedonic liking for sweet and fat tastes are linked with increased intakes of sweet and fatty tasting food groups and dietary patterns such as the ‘refined and processed’ and ‘fats and meat’ patterns. Taken together, the experimental studies described in this thesis provide evidence in support of a clear link between sweet taste and fat (creaminess) perception and dietary intake, particularly the intake of foods and dietary patterns characteristic of an individual’s taste phenotype. We also found that sweet taste and fat (creaminess) perceptions were not directly linked with body composition, metabolic biomarkers or endocrine regulators in this group of healthy, pre-menopausal women. Furthermore, higher intakes of the ‘refined and processed’ dietary pattern highlighted a pathway to obesity which appears to be mediated by changes in body composition and key endocrine regulators.
Figures re-used with publishers' permission.
Keywords: Women; New Zealand; Nutrition; Health and hygiene; Food; Sensory evaluation; Sweetness (Taste); Fat content; Heath aspects